The Influence of Parenting Patterns on the Character Development of Fishermen's Children in Ujungalang Village - Putri, Raudya Setya Wismoko; Setyowati, Dewi Liesnoor; Juhadi, Juhadi; Tjahjono, Heri (JURNAL HARMONI NUSA BANGSA, 2024)
This research aims to analyze the influence of parenting patterns on the character development of fishermen's children in Ujungalang Village, Kampung Laut District, Cilacap. The research method used is a descriptive method with a quantitative approach. Data was collected through questionnaires distributed to parents and children of fishermen as well as in-depth interviews with several key respondents. The research results show that parenting styles have a significant impact on children's character development. Democratic parenting, which is characterized by open communication and balanced supervision, has been proven to support the development of positive characters in children, such as independence, responsibility and self-confidence. On the other hand, authoritarian and permissive parenting tends to produce less than optimal characters, such as high dependency, lack of sense of responsibility, and low self-confidence. Apart from parenting styles, this research also found that environmental factors and family socio-economic conditions also influence the way parents care for their children. The conclusion of this research emphasizes the importance of parental awareness of the impact of parenting styles on children's character development, as well as the need for support from the environment and community to create conditions conducive to children's healthy and balanced development. It is hoped that this research can contribute to researchers, educational practitioners and policy makers in designing programs that support effective child care, especially in the context of fishing communities in coastal areas.